Household Food Insecurity and Malnutrition in an Urban Field Practice Area of a Medical College - Suhitha R Das; Chandana Krishna (Medsci Publications, 2018)
Introduction: The Global Hunger Index 2017 ranks India at 100 out of 118 countries. FAO estimates that about 190.7 million people are undernourished in India, which accounts for 14.5% of the pop- ulation. Food security is a fundamental human right for all citizens in its interim constitution. It is also a determinant of nutritional outcomes, especially for children. An adequate food intake, in terms of quantity and quality, is a key to healthy life. Malnutrition is the most serious consequence of food insecurity and has a multi- tude of health and economic implications. Objective: The study conducted to determine the prevalence of food insecurity at the household level and to assess the association between food insecurity and malnutrition of under-five children. Methodology: This cross-sectional study was conducted among the mothers of under-five children in urban field practice area of Sri Siddhartha Medical College, Tumkur. Household Food Insecu- rity Access Scale (HFIAS) was administered to the mother to assess the food insecurity and anthropometric measurements were taken for under-five children. Results: In the present study, the prevalence of food insecurity was 33.5%. There was a statistically significant association between food insecurity and wasting and under-nutrition. There was no as- sociation between food insecurity and stunting.